PENINGKATAN KEMAMPUAN MEMBACA PEMAHAMAN DENGAN MENGGUNAKAN STRATEGI PEMBELAJARAN INKUIRI SISWA KELAS XII. IPA. 2 SMA NEGERI 1 SUNGAI TARAB - Hildawitri, Hildawitri (FKIP UMSB, 2019)
The problem in this study is the lack of reading skills of students' understanding so that a strategy that is able to improve reading comprehension is needed. The purpose of this study was to describe an increase in reading comprehension using classroom student inquiry learning strategies 12 sains 2 high school number 1 sungai tarab. Relating to the theoretical problems used in this study are (1) the nature of reading, (2) the nature of reading comprehension, (3) inquiry learning strategy.Research data in the form of written learning outcome test results of the student observation sheet on learning reading comprehension skills by using student inquiry learning strategies 12 sains of high schoo number 1 sungai tarab. Procedure The study was conducted in 2 cycles consisting of 4 elements namely is (1) planning, (2) action, (3) observation or observation, and (4) reflection.The subject of this study was class students 12 sains 2 high school number 1 sungai tarab 32 people.Keywords read : reading, reasing comprehension, and inquiry learning.